Synthesis and characterization of a new bidentate Schiff base and its transition metal complexes - Temel, H; Ilhan, S; Sekerci, M (Taylor & Francis Inc, 2002)
The new bidentate Schiff base ligand L was synthesized by treating cinnamaldehyde with 1,2-bis(p-aminophenoxy)ethane. The complexes of Cu(II), Ni(II), Zn(II) and Mn(II) with the Schiff base have been characterized by magnetic susceptibility, conductance measurements, elemental analyses, IR, UV-Vis, H-1 and C-13 NMR studies. The analytical, conductance, spectral and magnetic data support the mononuclear formulations of these complexes with M:L = 1:2. In addition there are two hydroxo ligands present.
Keywords: Copper(Ii); Ni(Ii); Salicylaldehyde; Cobalt(Ii); Zinc(Ii); Ligand; Cu(Ii); Mn(Ii)